Systemic steroids and risk of fecal-oral shedding and increased transmission of SARS-CoV-2 in pemphigus cases - Pawar, Manoj (Clin Dermatol, 2020)
Pemphigus and its variants, viz., vulgaris, foliaceous, vegetans, Ig A pemphigus, paraneoplastic pemphigus and Senear-Usher syndrome are rare autoimmune blistering diseases of the skin and/or mucous membranes. The autoantibodies involved in the pathogenesis of pemphigus against desmoglein result in the breach of the skin and mucosal barrier, which acts as the first line of defence against pathogens. In this paper we underscore the importance of the integumentary system as a shield against the acquisition as well as transmission of SARS-CoV-2 virion. We have also made an attempt to delineate the various treatment modalities available and the viral-drug dynamics involved in choosing the optimum therapeutic modality.